Pedagogical Counseling as a Professional Activity of Specialists in the Field of Education - Saiuk, Valentyna (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2020)
The article reveals the essence of pedagogical counselling as a sphere of professional activity of specialists in the field of education. Specific features of pedagogical counselling that distinguish it from other types of counselling are defined and characterized. The main directions of professional activity of educational consultants are considered. Requirements for professional counsellors in the field of education are outlined.